Development of Prezi-Based Electronic Mind Map Learning Media on High School Animalia Biology Material - Julia Riska; Wan Syafii; Imam Mahadi (Journal of Educational Sciences, 2023)
The development of education continues to progress in the field of Information and Communication Technology (ICT) driving many changes, one of which is creating the concept of e-learning. The e-learning media in this study are electronic mind maps or prezi-based electronic mind maps. This research is research development (Research and Development), using the ADDIE development model (Analysis, Design, Develop, Implementation, and Evaluation). This research reached the learning media development stage or the development stage. The testing phase for the development of the e-mind map is analyzed in the form of validity (media validation, material validation, construct validation), practicality, and student responses. The results of the validation analysis are in the very valid category, practicality is in the very practical category used in learning, and student responses are in the very good category and are well received by students in learning.